{A mind for numbers} : how to excel at math and science (even if you flunked algebra) - Oakley, Barbara A., 1955- (New York : TarcherPerigree, an imprint of Penguin Random House, 2014)
Engineering professor Barbara Oakley knows firsthand how it feels to struggle with math. She flunked her way through high school math and science courses; but when she saw how her lack of mathematical and technical savvy were limiting her options post-graduation, she returned to college newly determined to retool her brain to master the subjects that had given her so much trouble. In A mind for numbers, Oakley draws on insights from neuroscience and cognitive psychology to reveal the secrets to effectively learning math and science.
Open the door -- Easy does it : why trying too hard can sometimes be part of the problem -- Learning is creating : lessons from Thomas Edison's frying pan -- Chunking and avoiding illusions of competence : the keys to becoming an "equation whisperer" -- Preventing procrastination : enlisting your habits ("zombies") as helpers -- Zombies everywhere : digging deeper to understand the habit of procrastination -- Chunking versus choking : how to increase your expertise and reduce anxiety -- Tools, tips, and tricks -- Procrastination zombie wrap-up -- Enhancing your memory -- More memory tips -- Learning to appreciate your talent -- Sculpting your brain -- Developing the mind's eye through equation poems -- Renaissance learning -- Avoiding overconfidence : the power of teamwork -- Test taking -- Unlock your potential.
Includes bibliographical references (pages 291-302) and index.
CSE
Keywords: Math anxiety; Mathematics -- Study and teaching -- Psychological aspects; Educational psychology; Computer science